ANALISIS DU PONT SYSTEM DALAM MENGUKUR KINERJA KEUANGAN PADA PERUSAHAAN JASA KONSTRUKSI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Fajar Rahmandiansyah; Sodikin Sodikin (Jurnal Ekonomi, Bisnis dan Social, 2023)
This research focuses on applying the Du Pont System to assess the financial performance of construction service companies listed on the Indonesia Stock Exchange over the past four years, from 2018 to 2021. The main objective of this study is to depict how the financial condition of these companies changed during that period using the Du Pont System. The analytical approach used is the Du Pont System, considering variables such as Net Profit Margin (NPM), Total Asset Turnover (TATO), Equity Multiplier (EM), Return On Investment (ROI), and Return On Equity (ROE). This research is causal-comparative in nature and employs a descriptive approach. The data utilized consists of secondary data obtained from the financial reports and annual reports of the companies, collected through a documentation method by visiting the website www.idx.co.id. The analysis results using the Du Pont System indicate that out of the nine companies studied, three of them have a Return On Investment level above the industry standard average. Therefore, it can be concluded that three out of the nine companies can be considered to have good financial performance.